Collapse, Reconfiguration or Renegotiation? The Strange End of the Mercian Kingdom, 850-924 - Insley, Charles (Reti Medievali Rivista, 2016)
The Kingdom of Mercians is generally assumed to have come to an end, largely as a result of Viking incursions, in the late ninth century; from the 880s its rulers seem to have been under the authority of Alfred the Great, king of the West Saxons. This essay argues that we should not see the end of the Mercian kingdom simply in terms of collapse, but also in terms of renegotiation, as the Mercian political elite sought, in the first few decades of the tenth century, to place themselves at the heart of a new political entity, the kingdom of the Anglo-Saxons, later the kingdom of the English.